Effectiveness Of Ranitidine Providing Compared With Omeprazol In Children With Gastroesofageal Reflux Disease - Hasri Salwan; Rizki Nandasari Sulbahri; Raden Muhammad Indra; Sri Kesuma Astuti (Jurnal RSMH Palembang, 2020)
Background. The drugs that are often given to children with GERD are stomach acidsuppressants, namely the H2 receptor antagonist and proton pump inhibitor (PPI) classof drugs, but the effectiveness of the two drugs is still controversial. Objective. Toevaluate the use of PPIs and H2 RA in children with GERD through evidence-basedcase studies. Methods. Systematic search for literature using the search instrumentPUBMED, Cochrane, Google Scholar, Pediatrica Indonesiana, and Sari Pediatri.Searches included systematic review articles, randomized controlled clinical trials andcohort studies. Abstract only studies, non-clinical evaluation results, and case reportswere excluded. Results. The study was obtained from three RCT studies comparingthe effectiveness of omeprazole and ranitidine in the treatment of GERD, all of whichhave differences. Azizollahi et al demonstrated that after 2 weeks of standard doses ofomeprazole or ranitidine there was a comparable significant improvement. Ummarinoet al demonstrated that omeprazole was significantly better than high-dose ranitidine.Cucchiara et al (1993) showed that high doses of ranitidine were as good as omeprazole.Another study by Pfefferkorn et al showed no significant effect on the addition ofomeprazole therapy combined with ranitidine in preventing the incidence of NAB. Astudy by Boccia et al comparing omeprazole, ranitidine, and non-therapy, found verylow relapse rates. Conclusion. Evidence regarding the use of ranitidine versusomeprazole in infants and children is lacking. Based on one study specifically in theinfant age group, omeprazole and ranitidine were of comparable effectiveness. A higherdose of ranitidine may have a better effect. In terms of complete symptom relief,omeprazole is likely to be superior to ranitidine.